P42/mnm - Christian Baerlocher; Lynne B. McCusker; David H. Olson (Atlas of Zeolite Framework Types, 2007)
Background Pediatric osteomyelitis is a serious bone infection whose early diagnosis remains challenging because clinical and laboratory findings are often nonspecific. Although Tc-99m methylene diphosphonate (MDP) bone scintigraphy is highly sensitive for detecting osteoblastic activity and multifocal disease, image interpretation remains largely qualitative and subject to interobserver variability. This study evaluated whether radiomics analysis of planar Tc-99m MDP bone scintigraphy could quantitatively differentiate infected from contralateral normal bone in children with suspected osteomyelitis. Methods This retrospective single-center study included 28 pediatric patients with suspected osteomyelitis who underwent anterior and posterior planar Tc-99m MDP bone scintigraphy. Paired infected and contralateral normal bone regions of interest (ROIs) of each patient were segmented. A standardized radiomics pipeline extracted 62 quantitative features per ROI, including shape, first-order intensity, and higher-order texture features. Statistical analyses included paired Wilcoxon signed-rank testing, effect size analysis, mutual information assessment, and leave-one-out cross-validated (LOOCV) logistic regression. A compact multivariable radiomics score was subsequently derived from the top-performing features. Results Texture-based radiomic features showed the strongest discrimination between infected and contralateral bone, with gray-level co-occurrence matrix-derived correlation and information-theoretic metrics - particularly T_InformationCorrelation2Averaged2D, T_InformationCorrelation2SliceMerged2D, and T_CorrelationAveraged2D/T_CorrelationSliceMerged2D - demonstrating highly significant differences (all P < 0.001) and large paired effect sizes (Cohen's d ≈ 0.80-0.85). Single-feature logistic regression models achieved moderate discrimination (LOOCV AUC: 0.60-0.63). Conclusion Planar Tc-99m MDP bone scintigraphy radiomics differentiated infected from normal contralateral bone in pediatric osteomyelitis, with texture-derived features outperforming intensity metrics (all P < 0.001; Cohen's d ≈ 0.80-0.85), supporting radiomics as an objective adjunct to visual interpretation.